Wetland restoration combined type ecological permeable gate

By using a new filter material composed of a high-strength outer layer and a spherical activated carbon core in the permeable gate passage of the wetland repair, the problems of insufficient strength and short maintenance time of the existing permeable gate material are solved, and efficient removal of water pollutants and long-term stable water purification effect of the gate is achieved.

CN119615848APending Publication Date: 2025-03-14国家林业和草原局西南调查规划院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411846806.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing sluice-permeable gate has limited adsorption effect, and the strength of the ceramic granules or activated carbon is insufficient, which is easy to lose under the erosion of the water flow, and the maintenance time is short.

Method used

A composite ecological permeability gate is designed, and a new type of filter material is arranged in its channel. The filter material is composed of a high-strength outer layer and a spherical activated carbon core. The outer layer materials include fly ash, steel slag, clay, pore-forming agent and binder, and a high-strength skeleton structure is formed by high-temperature roasting.

Benefits of technology

It realizes efficient removal of NH4+-N, P, and COD in the water body, and improves the long-lasting water purification capacity and service life of the permeable gate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615848A_ABST
    Figure CN119615848A_ABST
Patent Text Reader

Abstract

The invention discloses a wetland restoration combined type ecological permeable gate, and relates to the technical field of wetland ecological restoration, the wetland restoration combined type ecological permeable gate comprises a gate base, gates are arranged on the two sides of the gate base in an opposite supporting manner, a first channel is arranged between the two gates, a frame is obliquely arranged on the outer sides of the gates, a second channel is arranged between the gates and the frame, and a filter screen is arranged on the outer side of the frame; and filter materials are arranged in the channel I and the channel II. The novel filter material is arranged in the channel of the permeable gate, the strength is high, the adsorption rate of NH4 < + >-N, P and COD in the water body is high, and lasting water purification of the permeable gate can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wetland ecological restoration, and in particular to a wetland restoration composite ecological permeable gate. Background Art

[0002] Wetlands are important natural ecosystems, and the restoration of degraded wetlands helps maintain the stability and diversity of wetland ecosystems. There are many measures for the restoration of degraded wetlands, such as vegetation restoration, pest control, pollution control, sluice gate repair, and dike repair. Among them, sluice gate repair, as a measure of "wetland water source protection", focuses on annual restoration and management. During the low water level period, the original sluice gates in the source area and the water inlet or outlet of the lake area are maintained and updated with new sluice gates. The construction scope is not expanded. It can not only ensure the regulation of the water level of the lake in the dry season, but also timely ecological water replenishment. It can also intercept pollutants in the water quality entering or flowing out of the lake area. Therefore, it is currently widely used in the restoration of degraded wetlands.

[0003] The commonly used sluice gate repair method at present is also called ecological permeable sluice repair. Its main structure is the use of ecological gabions, that is, filling the inside of a rectangular cage with stones, expanded clay or activated carbon. As the water flows, a biofilm gradually grows in the gaps between the stones. On the one hand, it can intercept pollutants in the water body, and on the other hand, it can adsorb elements such as N and P in the lake water body to achieve water purification.

[0004] The main problems with the current permeable gates are: the adsorption effect of the stone itself is limited; the use of expanded clay or activated carbon has a large specific surface area and excellent adsorption performance, but due to the large number of surface pores and insufficient strength, its mass loss is large as the water flows, and the maintenance time is short. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a wetland restoration composite ecological permeable gate to address the deficiencies of the prior art. A new filter material is arranged in the channel of the permeable gate, which has high strength and can effectively remove NH 4+ -N, P, and COD removal rates are high, enabling long-term water purification through the permeable gate.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A wetland restoration composite ecological permeable gate comprises a gate base, gates are arranged on both sides of the gate base, channel one is between the two gates, frames are arranged obliquely on the outsides of the gates, channel two is between the gates and the frames, a filter is arranged on the outsides of the frames, and filter materials are arranged in channel one and channel two.

[0007] Furthermore, a gabion is arranged under the filter.

[0008] Furthermore, steel wire meshes are arranged in the channel one and the channel two, and filter materials are arranged in the steel wire meshes.

[0009] Furthermore, the filter material includes an inner core and an outer layer, the inner core is an activated carbon core with a particle size of 8-9 mm, and the thickness of the outer layer coated with the activated carbon core is 2-3 mm; the outer layer is made of the following raw materials in parts by weight: 56-60 parts of fly ash, 10-15 parts of steel slag, 10-15 parts of clay, 25-30 parts of pore-forming agent, and 15-20 parts of binder.

[0010] Furthermore, the pore-forming agent is a mixture of starch and calcium carbonate whiskers in a weight ratio of 1:2.

[0011] Furthermore, the binder is a mixture of sodium silicate and sodium carboxymethyl cellulose in a weight ratio of 1:1.

[0012] Furthermore, the activated carbon core is prepared by the following steps: After mixing phenolic resin, wood powder and sodium silicate, add 8-10% by mass of sodium carboxymethyl cellulose solution and mix well, extrude and granulate to obtain activated carbon balls with a particle size of 8-9 mm, heat to 300-450° C. and keep warm for 2 hours, cool to room temperature, and the weight ratio of the phenolic resin, wood powder, sodium silicate and sodium carboxymethyl cellulose is 5:5:2:0.2-0.3.

[0013] Furthermore, the filter material is prepared by the following steps: (1) The binder is prepared into a solution with a mass fraction of 10-15%, and the remaining outer layer raw materials are mixed evenly to obtain a mixture. The binder is sprayed on the inner core and then rolled to coat the mixture to obtain a filter material embryo; (2) After drying the green filter material at 90-100°C, heat it to 500°C and keep it at that temperature for 2 hours, then continue to heat it to 1150-1180°C and keep it at that temperature for 30-40 minutes, stop heating, and cool it to room temperature to obtain the filter material.

[0014] The beneficial effects of the present invention are: 1. The present invention discloses a wetland restoration composite ecological permeable gate, which has a gate base at the bottom, gates on both sides of the gate base, and a frame arranged obliquely on the outside of the gate, wherein the gate and the frame are both supporting frame structures, wherein filter materials are arranged in channel one and channel two for purifying water quality, and to prevent the filter materials from being blocked, a filter screen is arranged on the outside of the frame, which can intercept various suspended matter on the water-facing surface and be cleaned regularly. In addition, to ensure the structural stability of the permeable gate, stone cages are arranged at the bottom of the filter screen, that is, on both sides of the gate base, to fix the filter screen on the one hand, and to ensure the structural stability of the present application on the other hand.

[0015] 2. In order to increase the water quality restoration effect and restoration stability of this application, this application adopts a new type of filter material, which is divided into an inner core and an outer layer, wherein the inner core is a spherical activated carbon prepared by mixing phenolic resin and wood powder. In order to further increase its strength, a small amount of sodium silicate is added. Sodium silicate not only helps to shape, but also strengthens the structural strength of the activated carbon core in the activated carbon particles uniformly dispersed in the liquid phase formed during the roasting process. The outer layer is made of fly ash, steel slag and clay after firing. The glass phase of the fly ash floating beads melts and reconstructs during the high temperature process to form a new high-strength skeleton structure with high strength, low wear rate, and water erosion resistance, which can increase the service life of this application.

[0016] 3. To ensure the overall structural strength of the present application, sodium silicate is added to both the inner core and the outer layer. During high-temperature calcination, the liquid phase in the inner core is connected to the liquid phase in the outer layer, increasing the overall structural stability. In addition, the inner core is first preliminarily calcined, and the water and organic matter therein are decomposed to produce a large number of microporous structures. After being coated with the outer layer, it is further calcined at high temperature, and the sodium silicate at the junction of the inner core and the outer layer is melted and rebuilt, increasing the structural strength. At the same time, the pore-forming agent in the outer layer is slowly decomposed. Since calcium carbonate whiskers and starch are added to the pore-forming agent, a continuous pore structure can be formed in the outer layer, increasing the internal specific surface area and further increasing the water purification effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a structural schematic diagram of the present invention; Figure 2 It is a schematic diagram of the three-dimensional structure of the gate base of the present invention; Figure 3 The filter media has a NH 4+ -Adsorption curves of N, P, COD and the adsorption curve of COD of the comparative example. DETAILED DESCRIPTION

[0018] The present invention will be further described below in conjunction with the accompanying drawings and embodiments. Example 1

[0019] like Figure 1-2As shown, a wetland restoration composite ecological permeable gate is arranged at the entrance of the wetland lake to intercept domestic garbage and purify water quality. Combined with river regulation and lake base restoration projects, a rectangular cofferdam is first constructed during the low water level period, and then a gate base 1 is cast in place. Gates 2 are arranged on both sides of the gate base 1. The gates 2 are made of reinforced concrete. There is a channel 1 3 between the two gates 2. A frame 4 is arranged obliquely on the outside of the gate 2, which is a steel frame. There is a channel 2 5 between the gate 2 and the frame 4. Wire meshes are arranged in the channels 1 3 and 2 5, and filter materials are laid in the wire meshes. A filter screen 6 is arranged on the outside of the frame 4 to intercept domestic garbage, which can be cleaned regularly. A gabion 7 is arranged at the bottom of the filter screen 6, that is, the gabion 7 is arranged at the front and rear ends of the gate base 1 to ensure the structural stability of the present application and form an ecological permeable gate with a permeable wall mode.

[0020] In addition, soil can be piled up on the top of the gate base to plant plants. The roots of the plants will grow into the filter material, which can increase the water purification performance and ecology. Aquatic plant seeds can be placed inside the filter to enhance the water purification function of the permeable gate.

[0021] In order to increase the water purification effect of this application, the filter material in this application is a newly developed filter material, which includes an inner core and an outer layer. The inner core is an activated carbon core with a particle size of 8 mm. The thickness of the outer layer is 3 mm, and the outer layer is made of the following raw materials in parts by weight: 56 parts of fly ash, 15 parts of steel slag, 10 parts of clay, 25 parts of pore-forming agent, and 15 parts of binder.

[0022] The pore-forming agent is a mixture of starch and calcium carbonate whiskers in a weight ratio of 1:2; the binder is a mixture of sodium silicate and sodium carboxymethyl cellulose in a weight ratio of 1:1.

[0023] The activated carbon core is prepared by the following steps: After mixing phenolic resin, wood powder and sodium silicate, add 8% by mass fraction of sodium carboxymethyl cellulose solution and mix well, extrude and granulate to obtain activated carbon balls with a particle size of 8 mm, heat to 300°C and keep warm for 2 hours, and cool to room temperature. The weight ratio of the phenolic resin, wood powder, sodium silicate and sodium carboxymethyl cellulose is 5:5:2:0.2, wherein the wood powder can be wood powder such as wood powder, walnut shell, coconut shell powder, etc., and the present application uses wood powder.

[0024] The filter material is prepared by the following steps: (1) The binder is prepared into a solution with a mass fraction of 10%, and the remaining outer layer raw materials are mixed evenly to obtain a mixture. The binder is sprayed on the inner core and then rolled to coat the mixture to obtain a filter material green embryo; (2) After drying the green filter material at 90-100°C, heat it to 500°C and keep it for 2 hours. Then continue to heat it to 1150°C and keep it for 35 minutes. Stop heating and cool it to room temperature to obtain the filter material. Example 2

[0025] The filter material in Example 2 is different from that in Example 1 in that the filter material includes an inner core and an outer layer, the inner core is an activated carbon core with a particle size of 9 mm, the thickness of the outer layer coated with the activated carbon core is 2 mm, and the outer layer is made of the following raw materials in parts by weight: 58 parts of fly ash, 14 parts of steel slag, 12 parts of clay, 26 parts of pore-forming agent, and 18 parts of binder.

[0026] The pore-forming agent is a mixture of starch and calcium carbonate whiskers in a weight ratio of 1:2, wherein the calcium carbonate whiskers have a length of 50-80 μm and a diameter of 1-2 μm; and the binder is a mixture of sodium silicate and sodium carboxymethyl cellulose in a weight ratio of 1:1.

[0027] The activated carbon core is prepared by the following steps: After mixing phenolic resin, wood powder and sodium silicate, add 9% by mass sodium carboxymethyl cellulose solution and mix well, extrude and granulate to obtain activated carbon balls with a particle size of 9 mm, heat to 400°C and keep warm for 2 hours, and cool to room temperature. The weight ratio of the phenolic resin, wood powder, sodium silicate and sodium carboxymethyl cellulose is 5:5:2:0.25.

[0028] The filter material is prepared by the following steps: (1) The binder is prepared into a solution with a mass fraction of 12%, and the remaining outer layer raw materials are mixed evenly to obtain a mixture. The binder is sprayed on the inner core and then rolled to coat the mixture to obtain a filter material green embryo; (2) After drying the green filter material at 90-100°C, heat it to 500°C and keep it at that temperature for 2 hours. Then continue to heat it to 1160°C and keep it at that temperature for 35 minutes. Stop heating and cool it to room temperature to obtain the filter material. Example 3

[0029] The filter material in Example 3 is different from that in Example 1 in that the filter material includes an inner core and an outer layer, the inner core is an activated carbon core with a particle size of 9 mm, the thickness of the outer layer coated with the activated carbon core is 2 mm, and the outer layer is made of the following raw materials in parts by weight: 59 parts of fly ash, 12 parts of steel slag, 14 parts of clay, 28 parts of pore-forming agent, and 20 parts of binder.

[0030] The pore-forming agent is a mixture of starch and calcium carbonate whiskers in a weight ratio of 1:2; the binder is a mixture of sodium silicate and sodium carboxymethyl cellulose in a weight ratio of 1:1.

[0031] The activated carbon core is prepared by the following steps: After mixing phenolic resin, wood powder and sodium silicate, add 10% by mass sodium carboxymethyl cellulose solution and mix well, extrude and granulate to obtain activated carbon balls with a particle size of 9 mm, heat to 400°C and keep warm for 2 hours, and cool to room temperature. The weight ratio of the phenolic resin, wood powder, sodium silicate and sodium carboxymethyl cellulose is 5:5:2:0.3.

[0032] The filter material is prepared by the following steps: (1) The binder is prepared into a solution with a mass fraction of 14%, and the remaining outer layer raw materials are mixed evenly to obtain a mixture. The binder is sprayed on the inner core and then rolled to coat the mixture to obtain a filter material green embryo; (2) After drying the green filter material at 90-100°C, heat it to 500°C and keep it at that temperature for 2 hours. Then continue to heat it to 1180°C and keep it at that temperature for 35 minutes. Stop heating and cool it to room temperature to obtain the filter material. Example 4

[0033] The filter material in Example 4 is different from that in Example 1 in that the filter material includes an inner core and an outer layer, the inner core is an activated carbon core with a particle size of 9 mm, the thickness of the outer layer coated with the activated carbon core is 2 mm, and the outer layer is made of the following raw materials in parts by weight: 60 parts of fly ash, 10 parts of steel slag, 15 parts of clay, 30 parts of pore-forming agent, and 20 parts of binder.

[0034] The pore-forming agent is a mixture of starch and calcium carbonate whiskers in a weight ratio of 1:2; the binder is a mixture of sodium silicate and sodium carboxymethyl cellulose in a weight ratio of 1:1.

[0035] The activated carbon core is prepared by the following steps: After mixing phenolic resin, wood powder and sodium silicate, add 10% by mass sodium carboxymethyl cellulose solution and mix well, extrude and granulate to obtain activated carbon balls with a particle size of 9 mm, heat to 300-450°C and keep warm for 2 hours, cool to room temperature, and the weight ratio of the phenolic resin, wood powder, sodium silicate and sodium carboxymethyl cellulose is 5:5:2:0.3.

[0036] The filter material is prepared by the following steps: (1) The binder is prepared into a solution with a mass fraction of 15%, and the remaining outer layer raw materials are mixed evenly to obtain a mixture. The binder is sprayed on the inner core and then rolled to coat the mixture to obtain a filter material green embryo; (2) After drying the green filter material at 100°C, heat it to 500°C and keep it at that temperature for 2 hours. Then continue to heat it to 1180°C and keep it at that temperature for 35 minutes. Then stop heating and cool it to room temperature to obtain the filter material.

[0037] Comparative Example 1 Comparative Example 1 is a comparative example of Example 4, and the filter material is activated carbon balls with a particle size of 11 mm.

[0038] Comparative Example 2 Comparative Example 2 is a comparative example of Example 4, and the filter material is prepared by the following steps: (1) The binder is prepared into a solution with a mass fraction of 15%, and the remaining outer layer raw materials are mixed evenly, and extruded into granules to obtain filter material green embryos with a particle size of 11 mm; (2) After drying the green filter material at 100°C, heat it to 500°C and keep it at that temperature for 2 hours. Then continue to heat it to 1180°C and keep it at that temperature for 35 minutes. Then stop heating and cool it to room temperature to obtain the filter material.

[0039] 1. Performance testing: The compressive strength and porosity of the filter materials prepared in the present application and comparative examples 1-2 were tested, wherein 20 filter materials were randomly selected, the compressive strength of each filter material was measured, and then the average value was taken; the porosity was measured with reference to the test method of GJ / T299-2008 "Artificial ceramsite filter material for water treatment", and the wear rate was measured with reference to GB / T 12496.6-1999 standard.

[0040] 2. Filter column adsorption test: The filter column is a self-designed organic glass cylinder (inner diameter 12 cm, height 100 cm) filled with filter material (height 80 cm). Water flows into the cylinder from bottom to top through a water pump. Water samples are collected at the inlet and outlet of the filter column to measure the NH 4+ -N, P, COD and other related water quality indicators.

[0041] The reactor is injected with activated sludge from the sewage treatment plant, with the sludge volume accounting for one-fourth of the filter volume, and the experimental wastewater is injected for aeration. After 3 days of aeration, the muddy water in the reactor is drained. Then the experimental wastewater is pumped in. The experimental wastewater indicators are: COD: 50-60mg / L, ammonia nitrogen (NH4 + -N): 30. 36~40.25mg / L, phosphorus P: 9.12-11.65 mg / L, inlet flow rate is 9.04L / h (residence time 1h), dissolved oxygen 6.0mg / L, COD and NH 4+ -N, P concentration, calculate the average removal rate for 7-21 days, the results are shown in Table 1; Example 4 for NH 4+ -N, P, COD adsorption curves and comparative example 1-2 COD adsorption curves see Figure 3 .

[0042] Table 1 Performance test data It can be seen from Table 1 that the filter material prepared in this application has a particle size of 9-10 mm, a porosity of 57-63%, a wear rate of ≤1.01%, ammonia nitrogen removal rate of 95.4-97.7%, a P removal rate of 93.5-94.7%, and a COD removal rate of 91.3-93.2%. That is, the filter material prepared in this application has high strength, low wear rate, erosion resistance, and high porosity, and can remove NH in water. 4+ -N, P, COD has a strong adsorption effect. Combining Comparative Examples 1 and 2, it can be seen that the filter material composed of the inner core and the outer layer of the present application can greatly improve its compressive strength, reduce the wear rate, and improve the water purification effect.

[0043] Combination Figure 3 It can be seen that the application has excellent adsorption performance, and on the third day, the adsorption of NH4 + The removal rates of -N, P, and COD have been maintained at a high level, and remain stable after the 5th day, and can still remain stable after 21 days, but the water purification effects of Comparative Examples 1 and 2 begin to decline after 15 days, especially the decline of Comparative Example 2, indicating that the filter material prepared in Comparative Example 2 has poor biological adhesion, and the filter material is easily clogged and has poor adsorption stability. In addition, it can also be shown that the filter material prepared by the technical solution of the present application can maintain a long-term and stable water purification effect.

[0044] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.

Claims

1. A wetland restoration composite ecological permeable gate, comprising a gate base (1), characterized in that: Gates (2) are arranged on both sides of the gate base (1), a channel one (3) is formed between the two gates (2), a frame (4) is arranged obliquely on the outside of the gates (2), a channel two (5) is formed between the gates (2) and the frame (4), a filter screen (6) is arranged on the outside of the frame (4), and filter materials are arranged in the channel one (3) and the channel two (5).

2. A wetland restoration composite ecological water-permeable gate according to claim 1, characterized in that: A gabion (7) is arranged at the bottom of the filter screen (6).

3. The wetland restoration composite ecological water-permeable gate according to claim 1, characterized in that: Steel wire meshes are arranged in the channel one (3) and the channel two (5), and filter materials are arranged in the steel wire meshes.

4. The wetland restoration composite ecological water-permeable gate according to claim 1, characterized in that: The filter material includes an inner core and an outer layer, wherein the inner core is an activated carbon core with a particle size of 8-9 mm, and the thickness of the outer layer coated with the activated carbon core is 2-3 mm; the outer layer is made of the following raw materials in parts by weight: 56-60 parts of fly ash, 10-15 parts of steel slag, 10-15 parts of clay, 25-30 parts of pore-forming agent, and 15-20 parts of binder.

5. The wetland restoration composite ecological water-permeable gate according to claim 4, characterized in that: The pore-forming agent is a mixture of starch and calcium carbonate whiskers in a weight ratio of 1:

2.

6. The wetland restoration composite ecological water-permeable gate according to claim 4, characterized in that: The binder is a mixture of sodium silicate and sodium carboxymethyl cellulose in a weight ratio of 1:

1.

7. The wetland restoration composite ecological water-permeable gate according to claim 4, characterized in that: The activated carbon core is prepared by the following steps: After mixing phenolic resin, wood powder and sodium silicate, add 8-10% by mass of sodium carboxymethyl cellulose solution and mix well, extrude and granulate to obtain activated carbon balls with a particle size of 8-9 mm, heat to 300-450° C. and keep warm for 2 hours, cool to room temperature, and the weight ratio of the phenolic resin, wood powder, sodium silicate and sodium carboxymethyl cellulose is 5:5:2:0.2-0.

3.

8. The wetland restoration composite ecological permeable gate according to claim 4 is characterized by: The filter material is prepared by the following steps: (1) The binder is prepared into a solution with a mass fraction of 10-15%, and the remaining outer layer raw materials are mixed evenly to obtain a mixture. The binder is sprayed on the inner core and then rolled to coat the mixture to obtain a filter material embryo; (2) After drying the green filter material at 90-100°C, heat it to 500°C and keep it at that temperature for 2 hours, then continue to heat it to 1150-1180°C and keep it at that temperature for 30-40 minutes, stop heating, and cool it to room temperature to obtain the filter material.